2023
DOI: 10.1111/jmwh.13478
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Self‐Efficacy as a Mediator in the Relationship Between Postpartum Depression and Maternal Role Competence: A Cross‐Sectional Survey

Abstract: IntroductionThis study aimed to (1) examine the relationships among postpartum depression, maternal self‐efficacy, and maternal role competence, and to (2) test whether maternal self‐efficacy mediates the relationship between postpartum depression and maternal role competence.MethodsUsing a cross‐sectional design, we conveniently sampled 343 postpartum mothers from 3 primary health care facilities in Eswatini. Data were collected using the Edinburgh Postnatal Depression Scale, Maternal Self‐Efficacy Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Various factors, including low social support, poor self-esteem, unpreparedness for pregnancy, family dysfunction, challenging infant temperament, and infant and maternal health issues, are connected to inadequate maternal role competence. In Dlamini and colleagues’ study, mothers who had received antenatal education exhibited better self-efficacy compared to those who had not [ 40 ], emphasizing the importance of this intervention. The studies also found a correlation between strong maternal self-efficacy and increased maternal role competency.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Various factors, including low social support, poor self-esteem, unpreparedness for pregnancy, family dysfunction, challenging infant temperament, and infant and maternal health issues, are connected to inadequate maternal role competence. In Dlamini and colleagues’ study, mothers who had received antenatal education exhibited better self-efficacy compared to those who had not [ 40 ], emphasizing the importance of this intervention. The studies also found a correlation between strong maternal self-efficacy and increased maternal role competency.…”
Section: Resultsmentioning
confidence: 99%
“…The studies also found a correlation between strong maternal self-efficacy and increased maternal role competency. Furthermore, this is linked with reduced postpartum depression symptoms [ 32 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations